USING MATHEMATICAL MODELING FOR OPTIMIZATION SOLAR POWER SYSTEM’S OPERATION - Калініченко, А. В.; Титко, Р.; Сакало, В. М.; Горб, О. О. (Scientific Progress & Innovations, 2014)
Possibilities of the use of mathematical modeling in creation, analysis and implementation heliosystems based on data obtained in the laboratory of renewable energy. As a result, the research revealed the peculiarities of the selected parameters of the solar heat exchanger performance. The efficacy of vacuum solar collector and the simulation results proved the feasibility of using this type of equipment.